Pioneering the use of micro-biomarkers in oral cancer detection - Namrutha D Shekar; L. Kayal; N. Aravindha Babu; Mukesh Kumar Dharmalingam Jothinathan; Iadalin Ryntathiang (Oral Oncology Reports)
This critique analyzes the role of dietary habits on the vigorous field of oral microbiome studies and the treatment of oral cancer. It brings into light the multi-system interaction between the oral microbiota which not only look at the known pathogenic bacteria such as Porphyromonas gingivalis and Fusobacterium nucleatum but the overall mechanism by which oral cancer develops. Molecular markers that microbes leave behind while colonizing a cancerous site may serve as windows into early diagnosis and prevention. Two examples of these are Corynebacterium and Fusobacterium. In reverse, though, the sampling inconsistency and limited picture of the interactions between microbes remain the main obstacles. Therefore, this review underlines the position of omics technology which helps us understand the role of microbiome and possibly its contribution in cancer development. Also, these studies should be conducted for the long term as it is expected to produce a comprehensive view. On the other hand, it scrutinizes formulation and application of microbiota stabilizers, such as prebiotics and probiotics in individualized anticancer therapy. On a positive side, the implication about this review is that oral microbial dysbiosis together with microbial biomarkers play a pivotal role and although the mechanism of disease is clearly depicted, consequently, it paves a way for patient-centered treatment approaches.